Atención al cliente en la Heladeria Stefy Gelato 2 del cantón Puebloviejo 2021 - Herrera Monserrate, Jahaira Yomira (2021)
Customer service is a definitely important component within all organizations or companies without exceptions, due to this it is required that the collaborator has culture when serving the consumer, any customer who buys a product is deserving of a cordial, attentive treatment and helpful. Any company is very important to carefully plan those tasks that have to do with direct contact with the customer. Although many times we do not realize it, our clients are our most precious asset since thanks to them the company can survive. Therefore, every company, organization or independent professional must be clear that their strategies, actions and objectives must be directed towards the client. This case study was carried out with the objective of knowing and analyzing the factors that affect customer service in the business, based on the skills of the staff, needs, expectations, and customer satisfaction, taking into account that they are the part essential for the business and thus be able to achieve a favorable level of sales, and customer loyalty.